Peranan Pendidik Dalam Membimbing Peserta Didik Diskalkulia Pada Kelas V SDN Kebonromo 3 Kecamatan Ngrampal Kabupaten Sragen Tahun Pelajaran 2015/2016 - Ayuningtyas, Deti Meilita (2016)
This study describes the case of difficulty arithmetic (dyscalculia) in class V SDN Kebonromo 3. Treatment for learners dyscalculia should be done with the cooperation between the school and the families so that learners can follow any learning dyscalculia more friends. This research aims to determine the difficulties experienced by learners dyscalculia, knowing the efforts of educators to learners dyscalculia and determine the role of educators in guiding learners dyscalculia in class V SDN Kebonromo 3 Ngrampal District of Sragen in the school year 2015/2016, amounting to 15 learners, while dyscalculia 3 learners. This research uses descriptive qualitative and case study design. Data collection methods used were interviews, observation, documentation and field notes. Results of this study indicate that guidance to learners dyscalculia in SDN Kebonromo 3 is optimal from the school. Lack attention of parents/guardians at home to educate and guide learners dyscalculia led to the school and the parent/guardian has not fully cooperate in addressing the participants dyscalculia students. Learners dyscalculia is still experiencing difficulties in distinguishing symbols, subtraction, multiplication, division and have not fluent in reading. Efforts and the role of educators committed to learners dyscalculia is to provide additional hours after school, follow course in out of school, giving specific issues, additional time is currently working on, repeating the material has been submitted, giving motivation and reward, using props, methods in learning activities and give sugestion and spirit to students with dyscalculia. Keywords: the role of educator, dyscalculia.